Fostering Effective Teaching Practices: An Analysis of Classroom Implementation Among Pre-Service Indonesian Language Teachers - Ngatmini Ngatmini; Suyitno Suyitno (Indonesian Language Education and Literature, 2025)
Teacher competency plays a crucial role in enhancing educational quality, yet many Indonesian pre-service teachers struggle to translate pedagogical theory into effective classroom practice. This study analyzed classroom implementation among pre-service Indonesian language teachers participating in the Teacher Professional Education Program (PPG). Using a descriptive-qualitative design during the 2024 PPG performance test (UKIN) in Central Java, data were collected from lesson plans and classroom observations of 18 participants aged 21–25. Teaching performance was evaluated using a validated rubric covering seven competencies: greeting and rapport, lesson setting, activating prior knowledge, engagement and motivation, creating a positive environment, introducing new concepts, and managing time and pacing. Results indicate strong performance in creating positive learning environments (77.8%) and setting lessons (72.2%), while activating prior knowledge (44.4%) and time management were the weakest. The findings reveal a persistent gap between theoretical knowledge and practice. Theoretically, the study reinforces microteaching and classroom management frameworks by illustrating how pre-service teachers operationalize basic teaching competencies. Practically, it provides evidence-based implications for improving PPG training through targeted exercises in knowledge activation, pacing, and student-centered pedagogy, helping teacher educators design more responsive and practice-oriented preparation models.Menciptakan Praktik Pengajaran yang Efektif: Analisis Implementasi di Kelas pada Guru Prajabatan Bahasa IndonesiaKompetensi guru memainkan peran penting dalam meningkatkan kualitas pendidikan, namun banyak guru prajabatan di Indonesia kesulitan menerjemahkan teori pedagogis ke dalam praktik kelas yang efektif. Studi ini menganalisis implementasi di kelas di antara guru bahasa Indonesia prasekolah yang berpartisipasi dalam Program Pendidikan Profesi Guru (PPG).  Menggunakan desain deskriptif-kualitatif selama uji kinerja PPG (UKIN) tahun 2024 di Jawa Tengah, data dikumpulkan dari rencana pembelajaran dan observasi kelas 18 peserta berusia 21–25 tahun.  Kinerja mengajar dievaluasi menggunakan rubrik yang divalidasi yang mencakup tujuh kompetensi: sapaan dan hubungan, pengaturan pelajaran, mengaktifkan pengetahuan sebelumnya, keterlibatan dan motivasi, menciptakan lingkungan positif, memperkenalkan konsep baru, serta manajemen waktu dan kecepatan.  Hasil menunjukkan kinerja yang kuat dalam menciptakan lingkungan belajar positif (77,8%) dan mengatur pelajaran (72,2%), sementara mengaktifkan pengetahuan sebelumnya (44,4%) dan manajemen waktu adalah yang terlemah.  Temuan ini mengungkapkan kesenjangan yang persisten antara pengetahuan teoretis dan praktik.  Secara teoretis, penelitian ini memperkuat kerangka kerja mikro-pengajaran dan manajemen kelas dengan mengilustrasikan bagaimana guru pra-jabatan mengoperasionalkan kompetensi dasar mengajar.  Secara praktis, ini memberikan implikasi berbasis bukti untuk meningkatkan pelatihan PPG melalui latihan yang ditargetkan dalam aktivasi pengetahuan, pengaturan kecepatan, dan pedagogi berpusat pada siswa, membantu pendidik guru merancang model persiapan yang lebih responsif dan berorientasi pada praktik.